1971
DOI: 10.1139/x71-034
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of an Ectomycorrhizal Fungus against the Root Pathogen Myceliumradicisatrovirens

Abstract: The ectomycorrhizal fungus Suillusgranulatus prevented the phytopathogenic fungus Myceliumradicisatrovirens from adversely affecting the growth of aseptically grown seedlings of Piceamariana. Disease symptoms caused by M. radicisatrovirens are summarized for aseptically grown pine and spruce seedlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…These symptoms are comparable to those observed by Richard et al (1971) for Picea mariana (Mill.) Seedlings inoculated with plugs of this fungus exhibited several symptoms, including chlorosis and necrosis of the needles.…”
Section: Fungal Culturessupporting
confidence: 89%
“…These symptoms are comparable to those observed by Richard et al (1971) for Picea mariana (Mill.) Seedlings inoculated with plugs of this fungus exhibited several symptoms, including chlorosis and necrosis of the needles.…”
Section: Fungal Culturessupporting
confidence: 89%
“…). Whereas the host benefits from the mycorrhiza‐mediated access to the plant growth‐promoting nutrients resulting from the saprotrophic activity of PAC, root colonization by PAC is constrained by the ECM mantle, which constitutes a physical and perhaps physiological barrier (Richard et al ., ). In fact, PAC biomass never exceeded 0.02 g per gram of root dry weight in dually inoculated roots, which is about 15 times less compared with the maximum PAC biomass in non‐mycorrhizal roots (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, colonization of established ectomycorrhizae (ECM) by PAC is significantly less frequent than that of nonmycorrhizal root tips (Grünig et al, 2008). Mycorrhizal fungi are known to protect plant seedlings against pathogens (Newsham et al, 1995;Azcó n-Aguilar & Barea, 1997;Whipps, 2004), and Richard et al (1971) showed that ECM formed by Suillus granulatus prevented DSE (probably PAC) from colonizing and adversely affecting Picea mariana seedlings. Similarly, PAC colonization of ECM of P. abies and Pseudotsuga menziesii was less frequent and less dense than that of nonmycorrhizal roots (V. Reininger, unpublished).…”
Section: Discussionmentioning
confidence: 99%